Relationships between stable isotope natural abundances (δ13C and δ15N) and water use efficiency in rice under alternate wetting and drying irrigation in soils with high clay contents - Wang, Zhenchang; Liu, Jinjing; Wang, Yaosheng; Agathokleous, Evgenios; Hamoud, Yousef Alhaj; Qiu, Rangjian; Hong, Cheng; Tian, Minghao; Shaghaleh, Hiba; Guo, Xiangping (Frontiers in Plant Science, 2022)
Natural abundance of the stable isotopecarbon (δ13C and δ15N) in plants is widely used to indicate water use efficiency (WUE). However, soil water and texture properties may affect this relationship, which remains largely elusive. Therefore, the purpose of this study was to evaluate δ13C as affected by different combinations of alternate wetting and drying irrigation (AWD) with varied soil clay contents in different organs and whole plant and assess the feasibility of using δ13C and δ15N as a physiological indicator of whole-plant WUE water use efficiency (WUEwhole-plant). Three AWD regimes, I100 (30 mm flooded when soil reached 100% saturation), I90 (30 mm flooded when reached 90% saturation) and I70 (30 mm flooded when reached 70% saturation) and three soil clay contents, 40% (S40), 50% (S50), and 60% (S60), were included. Observed variations in WUEwhole-plant did not conform to theoretical expectations of the organs δ13C (δ13Corgans) of plant biomass based on pooled data from all treatments. However, a positive relationship between δ13Cleaf and WUEET (dry biomass/evapotranspiration) was observed under I90 regime, whereas there were no significant relationships between δδ13Corgans and WUEET under I100 or I70 regimes. Under I100, weak relationships between δ13Corgans and WUEET could be explained by (i) variation in C allocation patterns under different clay content, and (ii) relatively higher rate of panicle water loss, which was independent of stomatal regulation and photosynthesis. Under I70, weak relationships between δ13Corgans and WUEET could be ascribed to (i) bigger cracks induced by water-limited irrigation regime and high clay content soil, and (ii) damage caused by severe drought. In addition, a negative relationship was observed between WUEwhole-plant and shoot δ15N (δ15Norgans15Nshoot) across the three irrigation treatments, indicating that WUEwhole-plant is tightly associated with N metabolism and N isotope discrimination in rice. Therefore, δ13C should be used cautiously as an indicator of rice WUEwhole-plant at different AWD regimes with high clay content, whereas δ15N could be considered an effective indicator of WUEwhole-plant.